The Effect Of Using Inquiry Based Teaching Assisted By The Boss Baby Cartoon On The Students’ Achievement In Learning Grammar - Rita Harisma; Nina Baijura Berutu (English Teaching and Linguistics Journal (ETLiJ), 2020)
This research was carried out  the effect of using Inquiry Based Teaching Assisted by The Boss Baby Cartoon on The Students’ Achievement in Learning Grammar. The  objective of this study described that Inquiry Based teaching Assited by The Boss Baby Cartoon on The Students’Achievement in LearningGrammar.This research has been conducted at SMA  SWASTA AL-HIKMA  JL. Marelan Raya Pasar 4 Barat. The population of this research was the tenth grade students of SMA SWASTA AL-HIKMA JL. MARELAN RAYA. Academic year 2019/2020. There were three classes of tenth years in this school with total number 108 students.Two classes were taken as sample. The researcher used cluster sampling.There were 68 students as sample that were divided into two classes, for experimental class (X MIA 2) consisted of 33 students and for control clas (X IIS 1)consisted of 35. The students had been given the multiple choice, which consisted 20 items. The finding showed that students who taught by using Inquiry Based Teaching got the better score than those who taught by using Listening Team,which was proven from the result of analysis showed that t-observed (5.24) was higher than t-table (1.66). It meant that alternative hyphothesis (Ha) was accepted.